Islam And the Malay world: an insight into the assimilation of Islamic values - Ishak, Mohd. Shuhaimi; Abdullah @ Chuah Hock Leng, Osman (IDOSI, 2012)
The spread of Islam to the Malay World, a term used to refer to the majority of Malay-Muslim dominated nations such as Indonesia, Malaysia, Brunei and the minority Malay-Muslim population of Vietnam, Cambodia, Thailand, Singapore and Philippines brought several changes. Before the arrival of Islam the Malay civilisation was characterised by Hindu and Buddhist influence. The impacts of Islamic civilisation from the West Asia to the Malay world are enormous. The Malays then had not only given up their polytheistic belief in many gods to the firm belief in Al-Tawhid, but had changed their life towards Islam. The Malays had fully adopted a life based on Islamic principles as evidenced in social and religious gatherings such as wedding ceremony, kenduri (feast) and doa selamat (acts of thanksgiving to Allah). This paper attempts to highlight the unique relation of Islam and the Malay world through the former’s expansion in terms of religious faith, assimilation of Islamic values in socio-religious life of the people, the roles of Islamic institutions such as mosques and madrasahs.